Law Students on Interdisciplinary, Problem‐Solving Teams: An Empirical Evaluation of Educational Outcomes at the University Of Denver's Resource Center for Separating and Divorcing Families. (30th January 2018) - Pruett, Marsha Kline; Schepard, Andrew; Cornett, Logan; Gerety, Corina; Kourlis, Rebecca Love
Abstract : Models of lawyering in separation and divorce disputes are evolving to emphasize interdisciplinary collaboration, problem solving, alternative dispute resolution, and changes in legal education that reflect these changes in practice. At the University of Denver's Resource Center for Separating and Divorcing Families (Center), supervised law and mental health graduate students worked as a team to provide assessment and service planning, mediation, therapy, and agreement drafting to parents. Evaluation results showed client satisfaction, and that students acquired new knowledge, skills, and values in line with a collaborative, problem‐solving orientation. Strengths and weaknesses of the model are considered. Key Points for the Family Court Community: Modern family law representation requires collaboration and problem‐solving skills. The Resource Center for Separating and Divorcing Families (RCSDF) is a model designed to educate law students into the practice of interdisciplinary, coordinated legal services that minimize the risks of the adversarial legal process for family well‐being after separation/divorce. An evaluation indicated that students increased in certain knowledge and skills (e.g., mediation, interviewing, financial planning, drafting agreements, preparing parenting plans) and in their comfort working in interdisciplinary teams. The evaluation also established that the interns provided competent services to clients who were very satisfied with the services rendered. If law schools want to be in the forefront of legal education, they should move in an interdisciplinary, problem‐solving direction that provides hands‐on opportunities for education and training.